Analisis Penentuan Saham Portofolio Optimal Dengan Model Indeks Tunggal Dalam Perusahaan yang Tergabung Indeks Kompas 100 Pada Bursa Efek Indonesia Periode 2013-2015 Studi untuk Perusahaan Perbankan - Frisma Novela Arisandy; M. Iskak Elly; Khusnik Hudzafidah (Fakultas Ekonomi Universitas Panca Marga, 2017)
This research aims to determine the optimal stock portfolio as the basis for the determination of investment in shares of companies at the Compas 100 Index listed on the Indonesia stock exchange. The research period is the period 2013-2015. This research is quantitative descriptive research. The population of the research is 36 companies at the Compas 100 Index listed on the Indonesia Stock Exchange period 2013–2015. The selection of the sample was determined by purposive sampling technique with the criteria is a company that continuously entered at the Compas 100 Index during the period of observation 2013–2015 and don't do stock split during that period, so that the obtained samples as many as 30 stocks sample, there are 20 stock that have return AGRO is 2.31%, BABP is 1.09%, BACA is 2.31%, BAEK is 0.24%, BBCA is 3.40%, BBKP is 2.31%, BBNP is 2.31%, BBMD is 4.87%, BBNI is 4.87%, BBRI is 25.41%, BBTN is 4.87%, BCIC is 1.09%, BDMN is 1.09%, BEKS is 1.09%, BJBR is 4.87%, BJTM is 4.93%, BKSW is 3.99%, BMAS is 1.09%, MEGA is 3.40%, BMRI is 23.15%. Expected return portfolio is 5,58% per month with risk is 4,17%. Keywords: Optimal Portfolio, A Single Index Model, Expected Return, Cut-Off Rate.